A novel modeling approach for a capacitated (S,T) inventory system with backlog under stochastic discrete demand and lead time - Pham Duc Tai; Pham Phuong Ngoc Huyen; Jirachai Buddhakulsomsiri (My University, 2020)
In this paper, a new period-based approach is proposed for modeling a capacitated inventory system, operating under an (S,T) policy with backlog. The system experiences stochastic discrete demand and lead time. By using the proposed method, a mathematical model is developed. The model can accurately estimate the inventory system measures of performance: the expected inventory on-hands and over-storage amount. Through a simulation experiment, the new model is compared with two other models, which are developed by using a widely used mean-based approach. The comparison is conducted based on a case study data set. The results demonstrate that the period-based model is superior to the mean-based models with respect to capturing the behaviors of the inventory system. Therefore, better inventory policy parameters can be obtained by employing the new model.
Keywords: Lead time; Stochastic modelling; Supply Chain and Inventory Management